Probing the the Glass Transition of Atactic Polystyrene Thin Films Using Fiber Optic Refractometry. Issue 1 (April 2014) - Giordano, M.; Russo, M.; Zarrelli, M.; Cusano, A.; Antonucci, V.; Heinrich, Gert; Wagenknecht, Udo
Summary An high resolution optical technique based on the film fiber optic refractometer has been used to investigate the effect of the thickness on the glass transition dynamic of Atactic Polystyrene films in the range 20–120 nm. The thermo‐optic behavior of a set of layers dip coated onto the fiber has been analyzed upon cooling from long term equilibrated melt state. The glassy transition temperature is observed to be thickness‐independent as did both the width and the lower and upper bounds of the transition itself. At lowering the thickness of the film the relevant effect is the reduction of the "contrast" between the melt equilibrium phase and the glassy state. A double layers model where a surface soft layer (3.9 nm at 418 K) do not contribute to the glass dynamic retaining liquid features even at temperature well below the glass transition, while the core layer shows a bulk glass transition, is able to quantitatively reproduce reflectance experimental data.